Ecophysiology and irrigation of the peanuts cultivated in second season - Coelho, Anderson Prates [UNESP]; Faria, Rogerio Teixeira de [UNESP]; Dalri, Alexandre Barcellos [UNESP] (Univ Estadual Centro-oeste, 2017)
The peanut crop is an excellent alternative for cultivation to farmers, whether in the agricultural field, being a good alternative for the succession and rotation of crops, whether in the financial sector, becoming a good source of income and profit for the farmers. Annual crops, such as peanuts, can usually be sown at any time of the year. However, due to the agricultural characteristics, climate, costs, market and logistics, many of them are directed only at a specific planting season. The summer crop, or first peanut crop, is responsible for almost all of the planted area in Brazil annually, in this way, the searches for the cultivation of crop are practically directed for this time. However, the cultivation of peanuts out of season, or second crop, has been gaining prominence due to its profitability, a fact due to both the best prices of the product on the market and for seed production. Thus, this work aims to gather technical information and characteristics of the cultivation of peanuts in the second season to reduce production risks. In addition, will focus on the use and management of irrigation, technology that is practically indispensable for the cultivation of peanuts in the second season.
Keywords: Irrigation management; Arachis hypogaea L.; Vegetative group; Climate risks